Penerapan Model Pembelajaran Inkuiri Terbimbing untuk Meningkatkan Hasil Belajar Peserta Didik SMA Pada Materi Elastisitas (Universitas Negeri Surabaya, 2022)
Today's learning is still too focused on memorizing concepts and memorizing formulas, so that physics learning is less meaningful. Basically, there are various learning models that can strengthen the approach and meet the needs of Curriculum 13 (revision). One of them is the guided inquiry learning model. This study aims to find out how much the effectiveness of learning using guided inquiry learning methods. The research method used by Pre Experimental Design with the design of one group pretest-posttest design is carried out in one class without comparison. To find out the results of the hypothesis test conducted t-test, obtained tcount > ttable (16.715 > 2.045). The decision of the test is to reject H0 and accept H1 so that from the data it can be said that there is a significant change in the final test results (post-test). To find out how much the effectiveness of guided inquiry learning methods was conducted the N-Gain test obtained a score of 0.56 including the category